Delays in making initial treatment contact after the first onset of mental health disorders in the Argentinean Study of Mental Health Epidemiology - Stagnaro, J.C. (2019)
Aims. While there are effective treatments for psychiatric disorders, many individuals with such disorders do not receive treatment and those that do often take years to get into treatment. Information regarding treatment contact failure and delay in Argentina is needed to guide public health policy and planning. Therefore, this study aimed to provide data on prompt treatment contact, lifetime treatment contact, median duration of treatment delays and socio-demographic predictors of treatment contact after the first onset of a mental disorder.Methods. The Argentinean Study of Mental Health Epidemiology (EAESM) is a multistage probability sample representative of adults (aged 18+) living in large urban areas of Argentina. A total of 2116 participants were evaluated with the World Mental Health Composite International Diagnostic Interview to assess psychiatric diagnosis, treatment contact and delay.Results. Projections of cases that will make treatment contact by 50 years taken from a survival curve suggest that the majority of individuals with a mood (100%) or anxiety disorder (72.5%) in Argentina whose disorder persist for a sufficient period of time eventually make treatment contact while fewer with a substance disorder do so (41.6%). Timely treatment in the year of onset is rare (2.6% for a substance disorder, 14.6% for an anxiety disorder and 31.3% of those with a mood disorder) with mean delays between 8 years for mood disorders and 21 years for anxiety disorders. Younger cohorts are more likely to make treatment contact than older cohorts, whereas those with earlier ages of disorder onset are least likely to make treatment contact. Those with anxiety disorders and major depressive disorder are more likely to make treatment contact when they have comorbid disorders, whereas those with substance use disorders are less likely.Conclusions. Argentina needs to implement strategies to get individuals with substance use disorders into treatment, and to reduce treatment delays for all, but particularly to target early detection and treatment among children and adolescents.